Educazione degli Adulti: politiche, percorsi, prospettive Studi in onore di Paolo Federighi - Boffo, Vanna; Del Gobbo, Giovanna; Torlone, Francesca (Studies on Adult Learning and Education, 2022)
The volume is made of a series of eighteen studies, all related to the key issues connected to the personal and professional path Paolo Federighi had in more than forty years. This is the time frame he dedicated to adult learning and education development, on a national level within the academic frame of the University of Florence and the institutional frame of ministries, regional and local governments, as well as on an international level being the founder and the first President of the European Association for the Education of Adults (EAEA), the founder of the European Association of Regional and Local Authorities for Lifelong Learning (EARLALL). Every study collected in the volume provides a broad and in-depth critical reflection on adult education in Italy and an overview of adult education policies in the non-teaching contexts.